Investigating the effects of filler material and heat treatment on hardness and impact strength of TIG weld. (2020) - Kumar, Aneesh; Dixit, Prashant Kumar
Abstract: Detailed experiments were conducted on AISI 304, 8 m austenitic plate TIG welded, to systematically investigate the effect of heat treatment and filler wire on the mechanical and microstructural properties. Hardness of the austenitic stainless steel when welded with TIG is more with 304 filler wire as compared to 308 filler wire. Existence of 90–100% austenitic phase results into good strength and high toughness value for the 308 filler wire weld in comparison with 304 filler wire weld. Due to heat treatment, the micro structure of base metal changes and most of the carbon found near the grain boundaries in chromium carbide formation also the stabilized ferrite and pearlite grain growth but also sulphide inclusion is more which with 308 filler wire and equiaxed grain growth with low ferrite and high austenite formed with little sulphide inclusion which indicates that 304 weld joint is more brittle in comparison with 308 filler wire weld.